An experiment was conducted to compare the utilization of tephrosia candida and leucaena leucocephala in mixtures with Panicum maximum as feed for small ruminants, using the artificial bag technique of feed evaluation. Three West African dwarf (WAD) sheep with rumen cannula were used for the experiment. T. candida was formulated into diets with P. maximum as diets A, B and C while L. leucocephala was formulated into diets with P. maximum as diets D, E and F in the ratio 3:1, 1:1 and 1:3 respectively for both legumes. The degradation characteristics indicated L. leucocephala – based diets as being more (P < 0.05) degradable in the rumen than the T. candida – based diets, with diet D having the highest potential degradability (a+b) value. (2013)
An experiment was conducted to compare the utilization of tephrosia candida and Leucaena leucocephala in mixtures with Panicum maximum as feed for small ruminants, using the artificial bag technique of feed evaluation. Three West African dwarf (WAD) sheep with rumen cannula were used for the experiment. T. candida was formulated into diets with P. maximum as diets A, B and C while L. leucocephala was formulated into diets with P. maximum as diets D, E and F in the ratio 3:1, 1:1 and 1:3 respectively for both legumes. The degradation characteristics indicated L. leucocephala – based diets as being more (P < 0.05) degradable in the rumen than the T. candida – based diets, with diet D having the highest potential degradability (a+b) value.